2016
DOI: 10.1016/j.stemcr.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

BMP-SMAD Signaling Regulates Lineage Priming, but Is Dispensable for Self-Renewal in Mouse Embryonic Stem Cells

Abstract: SummaryNaive mouse embryonic stem cells (mESCs) are in a metastable state and fluctuate between inner cell mass- and epiblast-like phenotypes. Here, we show transient activation of the BMP-SMAD signaling pathway in mESCs containing a BMP-SMAD responsive reporter transgene. Activation of the BMP-SMAD reporter transgene in naive mESCs correlated with lower levels of genomic DNA methylation, high expression of 5-methylcytosine hydroxylases Tet1/2 and low levels of DNA methyltransferases Dnmt3a/b. Moreover, naive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Reduced DNA methylation has been shown to cause disturbances, affecting the maintenance of embryonic and/or extra-embryonic cell identity and ESC differentiation ( Jackson et al., 2004 , Ng et al., 2008 , Sakaue et al., 2010 ). Reduced Bmp signaling in Smad1/5 DKO ESCs results in increased Dnmt3b levels, enhanced DNA methylation, and more efficient embryonic differentiation ( Gomes Fernandes et al., 2016 ). Consistent with enhanced Bmp signaling, we found that Smad2/3 DKO day 3 EBs display decreased Dnmt3b expression and increased expression of genes associated with DNA demethylation ( Tet2 and Gadd45b ) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced DNA methylation has been shown to cause disturbances, affecting the maintenance of embryonic and/or extra-embryonic cell identity and ESC differentiation ( Jackson et al., 2004 , Ng et al., 2008 , Sakaue et al., 2010 ). Reduced Bmp signaling in Smad1/5 DKO ESCs results in increased Dnmt3b levels, enhanced DNA methylation, and more efficient embryonic differentiation ( Gomes Fernandes et al., 2016 ). Consistent with enhanced Bmp signaling, we found that Smad2/3 DKO day 3 EBs display decreased Dnmt3b expression and increased expression of genes associated with DNA demethylation ( Tet2 and Gadd45b ) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Smad2/3 double-mutant embryos, we find ectopic Bmp signaling throughout the distal VE. Studies also suggest that Bmp signaling promotes DNA hypo-methylation in ESCs ( Gomes Fernandes et al., 2016 ). It is tempting to speculate that Smad2/3 activities normally antagonize Bmp signaling and promote DNA methylation selectively in the early epiblast to maintain its developmental potential and prevent contributions to the extra-embryonic cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…For Nanog regulation, the shortest feedback is Nanog autoinhibition. This may have different number of intermediate steps due to involvement of histone acetylation [ 78 ], histone methylation [ 79 ], DNA methylation [ 80 , 81 ] or additional regulators [ 55 ]. The diversity of additional steps in Nanog autorepression can explain diverse unstable states represented by oscillations in the domain D 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This analysis highlighted a major difference between the R2i and 2i conditions in the regulation of pluripotency. It has previously been demonstrated that the augmented BMP4 signaling pathway plays a key role in R2i pluripotency, whereas it does not make a difference in the 2i condition ( Gomes Fernandes et al., 2016 , Hassani et al., 2014b ). Despite the high degree of similarity between the R2i and 2i conditions, as well as the strength of R2i in supporting pluripotency, i.e., in establishing and maintaining ESCs from single blastomeres ( Hassani et al., 2014a ) and embryonic germ cells from the PGCs of mice and rats ( Attari et al., 2014 , Mohammadi et al., 2015 ), these two conditions work in different ways.…”
Section: Discussionmentioning
confidence: 99%